Resolution - Stolz, George
1937-06 016a-0016-003 The representatives of the IFTU and the LSI, meeting at Geneva on the 16th and 17th June, 1937, state that, after the failure of the "control", which has become evident now, and in application of the London resolution, it is more than ever the duty of the two Internationals to call on all peoples to make an end, by all the means in their power, to the policy of continuous and large-scale intervention exercised by Italy and Germany under the cover of a policy so uncorrectly called "non-intervention", and that the delay in the withdrawal of foreigners fighting in Spain, which was so urgently demanded by the last Council of the League of Nations, is favouring the ends followed by Italy and Germany in Spain. They urge therefore the responsible bodies of the IFTU and LSI to meet at once in order to determine the steps be taken in respect of the resolution adopted in London by the Joint Conference of the two Internationals. 292/946/16a/18(iii)